Flexi-rigid Pleuroscopy in Diagnostics of Malignancy: A Narrative Literature Review - Salmiyah; Indra Yovi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Pleuroscopy is a less invasive treatment that allows access to the pleural cavity with the use of both visual and surgical equipment. This technique can be conducted with local anesthesia and mild sedation. Pleuroscopy is a medical procedure used for both diagnosis and treatment in the pleural cavity. Pleuroscopy enables direct observation of the pleural surface, enhancing the safety of procedures such as pleural biopsy, pleural fluid drainage, and pleurodesis. One purpose is to assist in verifying the diagnosis of cancer. This review was aimed to describe the use of flexi-rigid pleuroscopy in malignancy.